Prosedur Petty Cash: Insights di PT PLN (Persero) UP3 Banten Selatan - Melda Wani Siregar; Tri Wahyudi (Jurnal Inovasi Akuntansi (JIA), 2024)
Companies definitely need cash to operate, and if cash is managed properly, operations will run well. In carrying out its operations there will definitely be small costs, therefore PT PLN (Persero) UP3 Banten Selatan forms petty cash to pay for small operational activities. The purpose of this study was to determine how the petty cash procedures and internal control of petty cash carried out by PT PLN (Persero) UP3 Banten Selatan. This study uses a descriptive method, which shows the actual situation. The results show that PT PLN (Persero) UP3 Banten Selatan uses a fixed fund system or imprest system to provide petty cash with a maximum limit set by PT PLN (Persero) South Banten Distribution Unit (UID). PT PLN (Persero) UP3 Banten Selatan also conducted a review related to the organization of petty cash by implementing internal control on petty cash where internal control on petty cash carried out by PT PLN (Persero) UP3 Banten Selatan has been running well.